2015
DOI: 10.3389/fmicb.2015.01330
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Microbial Communities in Alpine Soils: Seasonal and Elevational Effects

Abstract: Microbial communities in alpine environments are exposed to several environmental factors related to elevation and local site conditions and to extreme seasonal variations. However, little is known on the combined impact of such factors on microbial community structure. We assessed the effects of seasonal variations on soil fungal and bacterial communities along an elevational gradient (from alpine meadows to a glacier forefield, 1930–2519 m a.s.l.) over 14 months. Samples were taken during all four seasons, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 61 publications
2
49
0
3
Order By: Relevance
“…The studies commonly show that microbial activity decreases with increasing elevation (Schinner, 1982 -Alps;Niklińska and Klimek, 2007 -Polish Carpathians;Margesin et al, 2009 -Alps), while there are no general altitudinal patterns in soil microbial diversity and community structure. For example, the microbial community composition did not change along elevational gradients in the Swiss Alps (Lazzaro et al, 2015), while other studies have documented decreasing bacterial (Ma et al, 2004 -western China;Lipson, 2007 -Rocky Mountains;Shen et al, 2013 -northeastern China) and fungal (Schinner and Gstraunthaler, 1981 -Alps) diversity with increasing altitude. Several studies reported a mid-altitudinal peak in microbial diversity (Fierer et al, 2011 -Peru;Singh et al, 2012 -Mt.…”
Section: Introductionmentioning
confidence: 71%
“…The studies commonly show that microbial activity decreases with increasing elevation (Schinner, 1982 -Alps;Niklińska and Klimek, 2007 -Polish Carpathians;Margesin et al, 2009 -Alps), while there are no general altitudinal patterns in soil microbial diversity and community structure. For example, the microbial community composition did not change along elevational gradients in the Swiss Alps (Lazzaro et al, 2015), while other studies have documented decreasing bacterial (Ma et al, 2004 -western China;Lipson, 2007 -Rocky Mountains;Shen et al, 2013 -northeastern China) and fungal (Schinner and Gstraunthaler, 1981 -Alps) diversity with increasing altitude. Several studies reported a mid-altitudinal peak in microbial diversity (Fierer et al, 2011 -Peru;Singh et al, 2012 -Mt.…”
Section: Introductionmentioning
confidence: 71%
“…Clones obtained from the same band with coinciding results are represented by a single clone a The number represents the band number (Fig. 1) and the letter the clone b Using 16S ribosomal RNA sequences (Bacteria and Archaea) database non-polluted soils support the idea that over the plant the major determinant of microbial community may be seasonal changes (Zhao et al 2016;Lacap et al 2007;Lazzaro et al 2015;Shi et al 2015;Streten-Joyce et al 2013;Žifčáková et al 2016;Hill et al 2015;Regan et al 2014), and/or soil type structure (Singh et al 2007). …”
Section: Discussionmentioning
confidence: 98%
“…SMCs follow distinct seasonal patterns across different habitats including boreal forest and arctic/alpine habitats (Schadt et al, 2003;Kuhnert et al, 2012;Lazzaro et al, 2012;Buckeridge et al, 2013;Koranda et al, 2013;Voříšková et al, 2014;Lazzaro et al, 2015;Schostag et al, 2015;Zifcakova et al, 2016) and are not at all dormant during winter. A community shift from bacteria towards cold-adapted fungi has been observed during winter (Schadt et al, 2003;Lazzaro et al, 2012;Buckeridge et al, 2013), with saprobial Ascomycota and basidiomycete yeasts-dominating fungal communities (Oberkofler and Peintner, 2008;Kuhnert et al, 2012).…”
Section: Introductionmentioning
confidence: 99%